Measurement of electrons from open heavy-flavor hadron decays in Au+Au collisions at √sNN = 200 GeV with the STAR detector - Abdulhamid, Muhammad Ibrahim; Deppner, Ingo Martin; Herrmann, Norbert; Leung, Yue; Söhngen, Yannick; Weidenkaff, Philipp (Journal of high energy physics, 2023)
We report a new measurement of the production of electrons from open heavy-flavor hadron decays (HFEs) at mid-rapidity (|y| < 0.7) in Au+Au collisions at $$ \sqrt{s_{NN}} $$= 200 GeV. Invariant yields of HFEs are measured for the transverse momentum range of 3.5 < pT < 9 GeV/c in various configurations of the collision geometry. The HFE yields in head-on Au+Au collisions are suppressed by approximately a factor of 2 compared to that in p + p collisions scaled by the average number of binary collisions, indicating strong interactions between heavy quarks and the hot and dense medium created in heavy-ion collisions. Comparison of these results with models provides additional tests of theoretical calculations of heavy quark energy loss in the quark-gluon plasma.
*STAR Collaboration: M.I. Abdulhamid, I.M. Deppner, N. Herrmann, Y.H. Leung, Y. Söhngen, P.C. Weidenkaff [sehr viele weitere Personen]
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol
Gesehen am 30.01.2024